Iron limitation-induced endophytic Ammoniphilus assemblage promotes root apoplastic iron remobilization by attenuation of salicylic acid pathways - Lin Zhu; Aijing Zhang; Jiansheng Guo; Huabing Liu; Yue Xie; Xiaomin Lu; Congsheng Yan; Jianfei Wang; Cheng Zhou (npj Biofilms and Microbiomes)
Abstract Plants establish symbiotic associations with root-colonizing microbes to adapt to adverse conditions. However, how root-associated microbiota interacted with their hosts to improve plant growth under nutrient deficient conditions remains poorly understood. In this study, we explored an interaction between tomato plants and root-associated microbiota under iron (Fe) limitation, mediated by bacterial secretion of glutamine. 16S rRNA gene sequencing revealed that Fe-limited conditions altered the composition of root-associated microbiomes, resulting in the enrichment of Ammoniphilus sp. This taxon was isolated and shown to alleviate Fe deficiency symptoms. Moreover, Fe deficiency triggered salicylic acid (SA)-induced hydrogen peroxide (H2O2) burst, thereby inhibiting the exudation of Fe-mobilizing phenolics from the roots. However, bacterial secretion of Gln greatly attenuated the SA-induced H2O2 production in the roots, thereby enhancing bacterial colonization and promoting apoplastic Fe remobilization. Collectively, these results underscored a microbial strategy for orchestrating plant SA pathways to facilitate the reutilization of root apoplastic Fe.